STRATEGI MANAJEMEN PESAN DAKWAH ISLAM DALAM EKOSISTEM MEDIA DIGITAL - Askolani, Muhammad (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah dan Komunikasi, Universitas Islam Bunga Bangsa Cirebon, 2025)
The development of the digital media ecosystem has created new spaces for the dissemination of Islamic da’wah messages that transcend geographical and demographic boundaries significantly. Amid these dynamics, technology-based applications such as Umma have emerged as specialized platforms designed to facilitate the spiritual needs of Muslims while managing the distribution of da’wah content in a structured and measurable manner. This study aims to analyze in depth the management strategies of Islamic da’wah messages implemented within the digital media ecosystem, with the Umma application as the main object of study. The discussion focuses on three key aspects that serve as the pillars of technology-based message management: content curation mechanisms, recommendation algorithm systems, and notification strategies used to reach users.This research employs a qualitative approach using document analysis methods, observation of application features, and systematic literature review. Data were collected through direct observation of the interface and features of the Umma application, analysis of content available on the platform, and review of literature including books and reputable scientific journals.The results show that the Umma application implements a comprehensive da’wah message management strategy through the integration of content curation based on Islamic values, personalization algorithms that consider user preferences, and optimized notification systems to encourage consistent spiritual engagement. These three strategies work synergistically to form an adaptive, personalized, and sustainable da’wah communication ecosystem. These findings provide important implications for the development of more effective and well-planned digital da’wah strategies in the future